Workplace Gender Dynamics and Mental Health: Does Family Harmony Mediate? - Fauziah, Dewi Rahmi; Muslim, M.; Anjani, Ega; Yunita, Irma (Management Department, Universitas Islam Negeri Alauddin Makassar, Indonesia, 2026)
This study aims to examine the effects of workplace gender dynamics and character education on the mental health of married working women, and to assess the mediating role of family harmony. This study advances HRM literature by repositioning family harmony as a boundary condition in work–family interface models, rather than a universal mediating mechanism. Using a quantitative design, data from 180 families in Banten Province, Indonesia, were analyzed with PLS-SEM. The findings reveal that character education does not significantly influence mental health, while workplace gender conditions exert a direct effect, with inequality increasing psychological strain. External factors, including income and number of children, remain more dominant predictors. Although both predictors influence family harmony, it does not mediate the relationship with mental health. These results imply that organizations and policymakers must prioritize gender-equitable work environments and integrated work–family policies to enhance women’s mental well-being.